Genetic Diversity and Molecular Characterization of Worldwide Prairie Grass (Bromus catharticus Vahl) Accessions Using SRAP Markers - Limei Yi; Zhixiao Dong; Yu Lei; Junming Zhao; Yanli Xiong; Jian Yang; Yi Xiong; Wenlong Gou; Xiao Ma (Agronomy, 2021)
Prairie grass (Bromus catharticus Vahl) is an important grass species that could be used in the production systems of certified seed and high-quality forage for grazing ruminants. In the present research, a sequence-related amplified polymorphism (SRAP) marker was employed to detect the genetic variability and structure of 80 prairie grass accessions from all over the world. Altogether, 460 reliable bands were amplified from 47 SRAP primer pairs with 345 (75%) polymorphic bands. The average values of discrimination power (DP) and polymorphic information content (PIC) were 0.753 and 0.317, respectively. Both the UPGMA clustering and PCoA analyses grouped the 80 accessions into five clusters, whereas the STRUCTURE analysis showed that 80 prairie grass accessions possessed three genetic memberships (K = 3). The results of the Mantel test showed that the distance matrix has a moderately positive correlation between the morphological and molecular data sets (r = 0.524). A poor genetic differentiation (Fst = 0.045) was discovered among the six geo-groups of accessions. Besides, the highest intragroup genetic diversity was found in the North America group (He = 0.335). This study provides a genetic structure and diversity case for prairie grass, and supplies new clues for the study and utilization of prairie grass.